Development Of Jelly Gum From Corn (Zea mays L.) And Tempeh (Rhizopus sp.) To Support Healthy Snacking In School-Aged Children - Murniadi, Ni Kadek Indah Oktavia; Nurhidayati, Vieta Annisa; Rizkiriani, Annisa (Universitas Pendidikan Indonesia, 2024)
Background: Unhealthy snacking remains a major nutritional issue among school-aged children in Indonesia. The consumption of jelly gum available in the market today has the potential to pose nutritional risks due to their high sugar content. This research aims to develop a healthy snack formula in the form of jelly gum for school-aged children using corn (Zea mays L.) and tempeh (Rhizopus sp.).Research Methods: This research is an experimental study carried out through several stages, namely idea development, product testing through standard recipes, production, proximate analysis, and product finalization.Research Result: The results of the study indicate that corn and tempeh jelly gum is potential to be a healthier snack choice for school-aged children compared to similar products in the market with lower fat and sugar content per serving size.Conclusion: Low-sugar jelly gum made from corn and tempeh is very suitable for school-aged children to prevent childhood obesity and diabetes